Smart Policies for Societies in Transition (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline thanks to generous funding support from The Swedish Governmental Agency For Innovation Systems, Vinnova. This timely book expertly examines ongoing pressing issues in the modern world namely, an unstable economic climate, political turmoil and the environmental crisis. It takes a unique look at how science, technology and innovation could contribute towards the creation of a smarter and more resilient society by allowing more inclusive approaches into how science is integrated.